Integrating Individual-Based Indices of Contaminant Effects - Christopher L. Rowe; William A. Hopkins; Justin D. Congdon (The Scientific World Journal)
Habitat contamination can alter numerous biological processes in individual organisms. Examining multiple individual-level responses in an integrative fashion is necessary to understand how individual health or fitness reflects environmental contamination. Here we provide an example of such an integrated perspective based upon recent studies of an amphibian (the bullfrog, Rana catesbeiana) that experiences several, disparate changes when larval development occurs in a trace elementcontaminated habitat. First, we present an overview of studies focused on specific responses of individuals collected from, or transplanted into, a habitat contaminated by coal combustion residues (CCR). These studies have reported morphological, behavioral, and physiological modifications to individuals chronically interacting with sediments in the CCR-contaminated site. Morphological abnormalities in the oral and tail regions in contaminant-exposed individuals influenced other properties such as grazing, growth, and swimming performance. Behavioral changes in swimming activities and responses to stimuli appear to influence predation risk in the contaminant-exposed population. Significant changes in bioenergetics in the contaminated habitat, evident as abnormally high energetic expenditures for survival (maintenance) costs, may ultimately influence production pathways (growth, energy storage) in individuals. We then present a conceptual model to examine how interactions among the affected systems (morphological, behavioral, physiological) may ultimately bring about more severe effects than would be predicted if the responses were considered in isolation. A complex interplay among simultaneously occurring biological changes emerges in which multiple, sublethal effects ultimately can translate into reductions in larval or juvenile survival, and thus reduced recruitment of juveniles into the population. In systems where individuals are exposed to low concentrations of contaminants for long periods of time, research focused on one or few sublethal responses could substantially underestimate overall effects on individuals. We suggest that investigators adopt a more integrated perspective on contaminant-induced biological changes so that studies of individual-based effects can be better integrated into analyses of mechanisms of population change.